Encapsulation of Au55 clusters within surface-supported metal-organic frameworks for catalytic reduction of 4-Nitrophenol - Liu, Jinxuan; Heidrich, Shahriar; Liu, Jianxi; Guo, Biao; Zharnikov, Michael; Simon, Ulrich; Wenzel, Wolfgang; Wöll, Christof (ACS applied nano materials, 2020)
We demonstrate a facile approach to encapsulate ligand-stabilized Au55 clusters [Au55(PPh3)12Cl6] within highly oriented surface-supported metal-organic framework (SURMOF) thin films via liquid-phase epitaxy. The Au55 clusters were successfully loaded into the pores of SURMOF during their fabrication, which has been confirmed by X-ray diffraction, infrared spectroscopy, and ultraviolet-visible spectroscopy. Computational modeling reveals that there is a strong interaction between the Au55 core and the oligophenyl ligands of the MOF pore, leading to a removal of the PPH3 ligands. The stabilized Au55 clusters within SURMOF exhibit excellent catalytic activity for the reduction of 4-nitrophenol.
Gesehen am 05.11.2021